Trade Agreements with Domestic Policies as Disguised Protection - LEE, Gea Myoung (Institutional Knowledge at Singapore Management University, 2007)
WTO rules prohibit “disguised protection” in the form of domestic policies. How then do governments cooperate over trade and domestic policies when none can verify whether a nation's domestic tax reduction is a protective measure or a reaction to a production externality? In this paper, each government privately observes whether a production externality associated with its import-competing good is high or low. This paper finds that in an optimal agreement, disguised protection with domestic policies is never used by governments with a high externality, and is never commonly realized. Moreover, in an optimal agreement, tariffs may be conditional on domestic policies.